FAKTOR PENGARUH TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR - Dame Ria Rananta Saragi (Universitas La Tansa Mashiro, 2024)
The research is to determine the effect of Sales Growth, Liquidity and Leverage on Profitability partially and simultaneously. The population in this study was 30 food and beverage sub-sector companies with a sampling technique based on criteria using purposive sampling. The samples obtained were based on the criteria of 30 food and beverage sub-sector companies. This type of research is quantitative with a causal associative approach. The data analysis technique used is quantitative with descriptive statistics using SPSS. Sales Growth partially has a positive and significant effect on Profitability, Liquidity has a partial positive and significant effect on Profitability, Leverage partially has a negative and significant effect on Profitability, and Sales Growth, Liquidity and Leverage simultaneously have a positive and significant effect on Profitability.